ASPEK HUKUM LINGKUNGAN HIDUP DALAM UPAYA MENCEGAH TERJADINYA KERUSAKAN DAN PENCEMARAN LINGKUNGAN HIDUP DI INDONESIA - Arifin Ma'ruf (Universitas Slamet Riyadi, 2018)
In Article 33 paragraph (3) of the 1945 Constitution which states that: 'earth and water and natural resources contained therein is controlled by the State and used for the greatest prosperity of the people